Biosimilars: An Approach to some Current Worldwide Regulation Frameworks - Esteban, Efraín; Bustos, Rosa-Helena; García, Julio-César; Jáuregui, Edwin (Current Clinical Pharmacology, 2019)
Developing new biologics has led to regulations and norms aimed at guaranteeing their safety, quality and effectiveness, in terms of marketing, prescription, use, interchangeability and switching. Biologics are of great importance in treating patients suffering from rheumatic, autoimmune, inflammatory and neoplastic diseases. The expiry/lapse of reference biologics or originators’ patents has meant that developing biosimilars involves accompanying legal requirements for their approval in countries worldwide. This paper has thus approached the situation of biosimilar regulation worldwide, the pertinent technical concepts and regulatory differences in some countries of interest.
Keywords: biotechnological drug/biopharmaceutical